On the methods of minimizing the risks of implementing artificial intelligence in the financial business of a company - Eugeny Yu. Shchetinin; Leonid A. Sevastianov; Anastasia V. Demidova; Tatyana R. Velieva (Discrete and Continuous Models and Applied Computational Science)
Effective application of artificial intelligence (AI) models in various fields in the field of financial risks can increase the speed of data processing, deepen the degree of their analysis and reduce labor costs, thereby effectively improving the efficiency of financial risk control. The application of AI in the field of financial risk management puts forward new requirements for the system configuration and operation mode of financial supervision. With the rapid growth of computer and network technologies, the increase in the frequency of market transactions, the diversification of data sources, and the development and application of big data, this creates new problems for financial risk management based on big data. This paper analyzes the role of artificial intelligence in promoting the reform and growth of the financial industry, and proposes countermeasures for the rational use of AI in the field of financial risk management.